Education on the Application of AI as a Strengthening of Digital Literacy in the Indonesian Pentecostal Church (GPI) Paya Kapar Congregation - Goldberd Harmuda Duva Sinaga; Irving Josafat Alexander; Fajar Gohanda Sinaga; Grace Sormin; Sunggu Sirait; Gloria Sirait (Jurnal Pengabdian Masyarakat Bangsa, 2026)
Improving digital literacy has become an essential need in today’s technological era, including within church communities, so that congregants can utilize technology wisely and productively. This study aims to analyze the impact of the AI Application Education as a Means to Strengthen Digital Literacy workshop on the knowledge, skills, and attitudes of congregants at GPI Paya Kapar. The method employed is descriptive-participatory within a community service framework, using data collection techniques such as observation, pre-test and post-test questionnaires, brief interviews, and activity documentation. The workshop was structured into three main sessions: theoretical presentation, hands-on practice using AI applications, and reflective discussion. The results indicate a significant improvement in participants’ knowledge of digital literacy and AI application, practical skills in using digital tools for learning and church activities, as well as more responsible attitudes and motivation in utilizing technology. These findings confirm the effectiveness of a participatory-educative, community-based approach in enhancing digital literacy and practical AI skills.